The critical reception of Sir Arthur Conan Doyle : Sherlock Holmes and beyond - Mazzeno, Laurence W. (Camden House, 2023)
"Twenty-first-century readers, television viewers, and moviegoers know Arthur Conan Doyle as the creator of Sherlock Holmes, the world's most recognizable fictional detective. Holmes's enduring popularity has kept Conan Doyle in the public eye. However, Holmes has taken on a life of his own, generating a steady stream of critical commentary, while Conan Doyle's other works are slighted or ignored. Yet the Holmes stories make up only a small portion of Conan Doyle's published work, which includes mainstream and historical fiction; history; drama; medical, spiritualist, and political tracts; and even essays on photography. When Doyle published - whatever the subject - his contemporaries took note. Yet, outside of the fiction featuring Sherlock Holmes, until recently relatively little has been done to analyze the reception Conan Doyle's work received during his lifetime and since his death. This book examines both academic and popular assessments of Conan Doyle's work, giving pride of place to the Holmes stories and their many adaptations for print, visual, and online media, but attending to his other contributions to turn-of-the-twentieth-century culture as well. The availability of periodicals and newspapers online makes it possible to develop an assessment of Conan Doyle's (and Sherlock Holmes's) reputation among a wider readership and viewership, thus allowing for development of a broader and more accurate portrait of Doyle's place in literary and cultural history"-- Provided by publisher.
Keywords: Doyle, Arthur Conan, -- 1859-1930 -- Criticism and interpretation -- History.; Doyle, Arthur Conan, -- 1859-1930 -- Appreciation.; Doyle, Arthur Conan, -- 1859-1930; LITERARY CRITICISM / American / General; Art appreciation; Criticism, interpretation, etc.; History; Literary criticism; Literary criticism.; Critiques littéraires.